Unveiling success factors for small and medium enterprises during COVID-19 pandemic. Issue 1 (1st January 2021) - Asad, Muzaffar; Kashif, Muhammad
Abstract: This research is being conducted on small and medium enterprises in order to explore the critical areas that have been affected because of COVID-19, so that concerned persons may pay special attention towards those areas. Small and medium enterprises have a significant contribution in gross domestic product, employment, and exports of developing countries. In order to explore the critical factors that have been affected because of COVID-19, a qualitative study has been designed and data was collected through interviews. Based on the literature, interview guide was developed. The owners, managers, and workers working in the small and medium enterprises have been chosen for interviews. After recording the interviews, the data was transcribed and coded. Finally, data reduction took place and significant factors were identified. It has been observed that because of COVID-19 several small and medium enterprises are at the verge of closure, and are facing huge losses. However, those small and medium enterprises that were innovative and explored opportunities in the crucial time not only survived, rather earned profits. Likewise, the management that was flexible, allowed their employees to work from home, and continued their operations with minimum delays in orders, performed in a sustainable way. The findings also revealed that government support, especially in deferring the taxes and provision of financial support, helped small and medium enterprises to survive during pandemic. The research findings are significant for the future researchers to empirically test the constructs and to develop theories for handling small and medium enterprises during crisis. The findings are significant for the policy makers as they can now better understand that which factors needed to be catered.